2011
DOI: 10.2165/11592430-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Excess Costs Associated with Patients with Pulmonary Arterial Hypertension in a US Privately Insured Population

Abstract: Patients with PAH had substantially higher costs and co-morbidity than controls, with circulatory/respiratory system-related costs accounting for 40% of excess costs. The high burden of illness suggests opportunities for savings from improved management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 22 publications
6
59
0
Order By: Relevance
“…Although this study is from a developing country, the association between lower SES and poorer health outcomes in patients with chronic disease is well documented in developed countries (7)(8)(9). Furthermore, economic burden (18), inequitable distribution of public services (34), adherence to treatment, and other factors may also exist in developed countries. The magnitude of the differentials in health and mortality can vary across countries with distinct economic, political, and social policies (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study is from a developing country, the association between lower SES and poorer health outcomes in patients with chronic disease is well documented in developed countries (7)(8)(9). Furthermore, economic burden (18), inequitable distribution of public services (34), adherence to treatment, and other factors may also exist in developed countries. The magnitude of the differentials in health and mortality can vary across countries with distinct economic, political, and social policies (51).…”
Section: Discussionmentioning
confidence: 99%
“…Wilkens and colleagues reported that each patient with PAH in Germany spends €47,400 per year on average, primarily due to drug costs (16,17). In the United States, the economic burden of privately ensured patients with PAH is substantial (18). In addition, low The funding sources provided financial support for the study but played no role in the study design or conduct, data collection and analysis, or the decision to submit the manuscript for publication.…”
mentioning
confidence: 99%
“…4 Patients with pulmonary arterial hypertension (PAH) have significantly higher health care costs and comorbidity than patients without PAH. 5 Thus an argument can be made for improved recognition and management of PH in diabetic individuals.…”
mentioning
confidence: 99%
“…This likely contributed to an accurate diagnosis and management of PAH at the expense of increasing healthcare costs [21]. A study by Kirson et al that analyzed a private insurance database from 2002-2007 demonstrated as compared to the general population patients with PAH had substantially higher costs and comorbidity resulting in 40% of excess costs associated with management and treatment of PAH patients [22]. On the contrary, management of PH WHO Group II & III is focused on treatment of the underlying disease.…”
Section: Health Utilization Costsmentioning
confidence: 99%